2021
DOI: 10.1111/bjd.20767
|View full text |Cite
|
Sign up to set email alerts
|

Modelling trajectories of parentally reported and physician‐confirmed atopic dermatitis in a birth cohort study*

Abstract: A.C. reports personal fees from Novartis, Thermo Fisher Scientific, Philips, Sanofi, Stallergenes Greer and AstraZeneca outside the submitted work. A.S. reports lecture fees from Thermo Fisher Scientific. C.S.M. reports personal fees from Novartis, grants and personal fees from GlaxoSmithKline and personal fees from Boehringer Ingelheim. T.S. and S.H. made an equal contribution to this work as joint first authors.A.S. and A.C. made an equal contribution as joint senior authors. Data availabilityThe data that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…30 This gene-environment interaction remained significant after adjusting for infantile eczema, suggesting that the effect of FLG genotype may be independent of eczema. 30 Furthermore, application of machine-learning and data-driven methods to longitudinally collected data in this cohort enabled discoveries of different eczema and wheeze phenotypes, 31,32 different subtypes of allergic sensitization, 33 and developmental trajectories and co-occurrence of eczema, wheeze and rhinitis. 34 Our recent study highlighted potential importance of such data-driven phenotypes in relation to peanut allergy by showing that different longitudinal trajectories of eczema differ in their association with comorbidities, including a 9-to 11-fold increase in the risk of peanut allergy among children in the persistent eczema, but not other eczema classes.…”
Section: Key Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…30 This gene-environment interaction remained significant after adjusting for infantile eczema, suggesting that the effect of FLG genotype may be independent of eczema. 30 Furthermore, application of machine-learning and data-driven methods to longitudinally collected data in this cohort enabled discoveries of different eczema and wheeze phenotypes, 31,32 different subtypes of allergic sensitization, 33 and developmental trajectories and co-occurrence of eczema, wheeze and rhinitis. 34 Our recent study highlighted potential importance of such data-driven phenotypes in relation to peanut allergy by showing that different longitudinal trajectories of eczema differ in their association with comorbidities, including a 9-to 11-fold increase in the risk of peanut allergy among children in the persistent eczema, but not other eczema classes.…”
Section: Key Messagesmentioning
confidence: 99%
“…34 Our recent study highlighted potential importance of such data-driven phenotypes in relation to peanut allergy by showing that different longitudinal trajectories of eczema differ in their association with comorbidities, including a 9-to 11-fold increase in the risk of peanut allergy among children in the persistent eczema, but not other eczema classes. 31 In the current analysis, we aimed to ascertain early-life predictors of peanut allergy and address a specific hypothesis that earlylife eczema and FLG loss-of-function mutations are independent risk factors. We then proceeded to investigate the association between previously derived longitudinal trajectories of sensitization, 33 wheeze 32 and allergic comorbidities, 34 and peanut allergy.…”
Section: Key Messagesmentioning
confidence: 99%
“…As the development and employment of machine learning and other data‐driven approaches gain popularity in healthcare, experts and government agencies have increasingly collaborated to develop guidelines to facilitate the growth of the field and delineate principles of best practice 45,46 . We further underline the need and benefit of cross‐disciplinary collaborations for the future of data‐driven research on AD and eczema 12 …”
Section: Discussionmentioning
confidence: 99%
“…In terms of atopic dermatitis, there seems to be inconsistency of findings about the association between FLG-LOF and different atopic dermatitis phenotypes with one study showing an inconsistent association between FLG genotype, a different definitions of atopic dermatitis. 37 Data from a UK and European cohort showed an association between FLG-LOF mutations and all definitions of atopic dermatitis (no atopic dermatitis, early-onset-persistent atopic dermatitis, early-onset-lateresolving atopic dermatitis, early-onset-early-resolving atopic dermatitis, mid-onset-resolving atopic dermatitis, and late-onsetresolving atopic dermatitis) other than mid-childhood onset of atopic dermatitis (UK cohort) and children with early-onset atopic dermatitis who outgrew their atopic dermatitis (EU cohort). 38 In terms of asthma, data from the COPSAC study (Denmark) 39 indicated an increased risk of developing recurrent wheeze, asthma, and asthma exacerbations in children with FLG-LOF mutations in the 1.5 years of life.…”
Section: Discussionmentioning
confidence: 99%